2016
DOI: 10.1111/all.13003
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 5 mediates corticosteroid insensitivity in airway smooth muscle in patients with severe asthma

Abstract: Background The mechanisms driving glucocorticoids (GC) insensitivity in patients with severe asthma are still unknown. Recent evidence suggests the existence of GC insensitive pathways in airway smooth muscle (ASM) caused by a defect in GC receptor (GRα) function. We examined whether other mechanisms could potentially explain the reduced sensitivity of ASM cells to GC in severe asthmatics. Methods ASM cells from healthy and severe asthmatic subjects were treated with TNFα and responses to corticosteroids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Our study indicated a correlation of elevated IL‐1β, TNF‐α and IFN‐γ, both in the serum and sputum, with the HADS‐D scores. In asthmatic populations, IL‐1β, TNF‐α and IFN‐γ are significantly associated with glucocorticoid treatment response and uncontrolled or severe asthma . Our previous study also indicated that over‐production of IFN‐γ would induce MyD88‐dependent steroid‐resistance in refractory asthma .…”
Section: Discussionmentioning
confidence: 72%
“…Our study indicated a correlation of elevated IL‐1β, TNF‐α and IFN‐γ, both in the serum and sputum, with the HADS‐D scores. In asthmatic populations, IL‐1β, TNF‐α and IFN‐γ are significantly associated with glucocorticoid treatment response and uncontrolled or severe asthma . Our previous study also indicated that over‐production of IFN‐γ would induce MyD88‐dependent steroid‐resistance in refractory asthma .…”
Section: Discussionmentioning
confidence: 72%
“…It is intriguing that IL-13 blockade modulates several aspects of different experimental models of allergic asthma (Laporte et al, 2001; Walter et al, 2001; Komai et al, 2003; Munitz et al, 2008; Chen et al, 2013; Ma et al, 2013; Chachi et al, 2017). Moreover, recent results demonstrate that anti-IL-13 antibody improves bronchial hyperresponsiveness and mucus production in a mouse model of non-allergic asthma (Gungl et al, 2018).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In the majority of patients, asthma can be controlled by combinations of inhaled glucocorticoids (ICS), short- or long-acting ß 2 -adrenergic agonists (LABA), long-acting muscarinic antagonists, and leukotriene receptor antagonists, according to the Global Initiative for Asthma (GINA) guidelines (GINA ). However, in approximately 15% of patients, the disease is refractory to conventional treatments (Chachi et al, 2013; Chachi et al, 2017) and results in hospital admissions due to severe exarcerbations (Sekiya et al, 2016; Kerkhof et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that an altered fatty acid metabolism and reduced stearoyl-coenzyme a desaturase activity in asthma [ 41 ]. Protein phosphatase 5 mediates corticosteroid insensitivity in airway smooth muscle in patients with severe asthma [ 42 ].…”
Section: Mechanismsmentioning
confidence: 99%